PERBANDINGAN UJI CBR LAPANGAN MENGGUNAKAN DCP DAN CBR LABORATORIUM PADA RUAS JALAN DALAM NEGERI HUTUMURI - Asmawan, Yayan; Kalalimbong, Abraham; Mansye Ronal (Jurnal Teknik Sipil dan Arsitektur, 2026)
The strength of the subsoil plays a very important role in the planning of road pavement structures. If the soil strength is insufficient, the road pavement may experience damage. Therefore, a soil investigation is necessary to identify the characteristics and bearing capacity of the soil. One method for measuring the soil's bearing capacity is through the calculation of the CBR (California Bearing Ratio) value. This study aims to examine the soil characteristics and compare the CBR values obtained from field measurements using a DCP (Dynamic Cone Penetrometer) with those obtained from laboratory testing. Based on the AASHTO classification, the soil in the road section in Hutumuri is classified as A-2-4, A-2-5, and A-2-7. The results of this study show that the lowest ratio between laboratory CBR and field CBR is 1:1.13 at point 3, while the highest ratio is 1:1.19 at point 1. Based on the obtained ratio, it appears that to determine the CBR value without conducting laboratory CBR testing, one can use a multiplier of 1.13 to 1.19 times the field CBR value obtained from the DCP test.